2020
DOI: 10.1002/ece3.6229
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in thermal acclimation and tolerance between populations of the winter ant, Prenolepis imparis

Abstract: Thermal phenotypic plasticity, otherwise known as acclimation, plays an essential role in how organisms respond to short‐term temperature changes. Plasticity buffers the impact of harmful temperature changes; therefore, understanding variation in plasticity in natural populations is crucial for understanding how species will respond to the changing climate. However, very few studies have examined patterns of phenotypic plasticity among populations, especially among ant populations. Considering that this intras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 87 publications
2
15
0
Order By: Relevance
“…We collected worker ants from a population on the UC Berkeley campus in Berkeley, California, USA (WGS1984; 122.26317, 37.87281), in June 2014. We chose this site because a previous study showed that P. imparis from this site exhibit phenotypic plasticity in response to both hot and cold temperatures [40]. After the ants were collected, they were immediately placed in one of three separate thermal conditions: (1) an incubator (Fisher Scientific Isotemp Model 650D Large 600 Series Incubator CAT# 11-690-650D) at 35˚C (heat stress), (2) on a roomtemperature bench-top approximately 21˚C, within the temperature range we expect to find their nests (a control), and (3) a walk-in cold room at approximately 5˚C (cold stress).…”
Section: Sample Collection and Stress Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…We collected worker ants from a population on the UC Berkeley campus in Berkeley, California, USA (WGS1984; 122.26317, 37.87281), in June 2014. We chose this site because a previous study showed that P. imparis from this site exhibit phenotypic plasticity in response to both hot and cold temperatures [40]. After the ants were collected, they were immediately placed in one of three separate thermal conditions: (1) an incubator (Fisher Scientific Isotemp Model 650D Large 600 Series Incubator CAT# 11-690-650D) at 35˚C (heat stress), (2) on a roomtemperature bench-top approximately 21˚C, within the temperature range we expect to find their nests (a control), and (3) a walk-in cold room at approximately 5˚C (cold stress).…”
Section: Sample Collection and Stress Exposurementioning
confidence: 99%
“…A detailed analysis of their nest structure in Florida found that nest chambers were dug 60 cm below ground, at temperatures between 16 and 24˚C [39]. A previous study found populations of P. imparis have different levels of plasticity and thermal tolerance [40] which makes this species an interesting candidate to examine the genetic basis of these traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured two well‐established proxies of cold‐ and heat stress resistance in insects, namely ‘chill‐coma recovery time’ (CCRT) and ‘heat knock‐down time’ (HKDT) (e.g. Bauerfeind & Fischer, 2014; Fischer et al, 2010; Stazione et al, 2020; Tonione et al, 2020). All individuals were tested for CCRT on day 2 of adult life and for HKDT the day after.…”
Section: Methodsmentioning
confidence: 99%
“…The capacity to recover rapidly from cold-induced coma is likely to be particularly relevant in environments where overnight temperatures (or other short-term fluctuations) are cold enough to prevent activity. In the winter ant, Prenolepis impairs, CCRT is faster in high altitude populations: (Tonione et al, 2020). In Drosophila species, CCRT has been related to thermal adaptation as it differentiates between species of tropical and temperate origin (Gibert et al, 2001).…”
Section: Introductionmentioning
confidence: 99%